Android-based Palembang Local Culture Procedure Text for Vocational High School: A Students’ Need Analysis - Ummy Wahyuni; Eryansyah Eryansyah; Rita Inderawati (AL-ISHLAH: Jurnal Pendidikan, 2022)
Rapid progress in science and technology is a hallmark of the globalized era. To stay up with the demands of the industry in the 4.0 era, it is important to consider both traditional classroom learning and social and virtual forms of learning. This research aims to discover, with the support of Palembang's vocational high school students and teachers, what kinds of reading material will best meet the demands of those pupils concerning procedure texts informed by the culture of that city. The author conducted an interview and a questionnaire to acquire data. Quantitative and qualitative assessments of the information were made. It was found that students needed English for their future careers, that they were not interested in reading because their English language skills were at a beginning level, that texts about general knowledge were relevant, that texts about Palembang's local culture were crucial as topics in reading comprehension, that texts about procedures where needed, and that reading materials about Palembang's local culture were not easily obtainable. Students in Palembang needed exposure to local culture, specifically Palembang's traditional dishes; 8) A mobile app for Android was needed to facilitate education. The assignment asked students to combine local Palembang culture with their English skills to produce a set of instructions using an Android app; this work could be useful in the students' professional lives in the future.